Wakarusa, Shawnee County - Simmons, Dillon (Kansas State University, The Chapman Center for Rural Studies, 2011)
The history of Wakarusa, a town in Shawnee County, Kansas, located about eleven miles south of Topeka, dates back to the 1850s. Its name originates from the Wakarusa River valley, land that was originally inhabited by the Pottawatomie Indians. The name "Wakarusa" was supposedly derived from an American Indian folk tale about a chief who crossed the river by horse and exclaimed to his followers, "Wa-ka-ru-sa," meaning "hip-deep" or "river of big weeds."
Dillon Simmons, “Wakarusa, Shawnee County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/59.
Keywords: Wakarusa; Wakarusa Hotel; Shawnee County; Santa Fe Railroad; Pottawatomie Indians; Zenas King